Pengaruh Sistem Bagi Hasil Deposito Terhadap Persepsi Nasabah - Devi Wahyu Arianti; Khodijah Ishak (Jurnal Perbankan Syariah)
Banking is a financial institution that provides services and facilities to its customers who wish to conduct financial transactions. Bank Syariah Mandiri is a sharia financial institution that offers mudharabah time deposits with a profit-sharing agreement. This study aims to determine the effect of the deposit sharing system on customer perceptions at Bank Syariah Mandiri Bengkalis Sub-Branch Office. This research uses quantitative methods with the number of respondents as many as 110 customers. Based on the results of the calculation of the correlation between profit-sharing with customer perceptions has a positive relationship. Then there is a significant influence between profit-sharing on customer perceptions at Bank Syariah Mandiri Bengkalis Sub Branch Office.